Contact Pathway Function During Human Whole Blood Clotting on Procoagulant Surfaces - Zhu, Shu; Herbig, Bradley A.; Yu, Xinren; Chen, Jason; Diamond, Scott L. (Frontiers in Medicine, 2018)
Microfluidic thrombosis assays allow the control of anticoagulation, hemodynamics, pharmacology, and procoagulant surfaces containing collagen ± tissue factor (TF). With corn trypsin inhibitor (CTI) ranging from low (1-4 ug/mL) to high levels (40-60 ug/mL), the function of Factor XIIa (FXIIa) can be modulated in the presence of low or high surface TF. With high CTI and no collagen/TF in the assay, no thrombin is generated during 15-min microfluidic perfusion. At low CTI (no TF), the generation of FXIa leads to fibrin polymerization at ~300 seconds after the initiation of flow over collagen, an onset time shortened at zero CTI and prolonged at high CTI. The engagement of FXIa was difficult to observe for clotting on high TF surfaces due to the dominance of the extrinsic pathway. Low TF surfaces allowed observable crosstalk between extrinsic pathway generation of thrombin and thrombin-mediated activation of FXIa, a feedback detected at >5 minutes and attenuated with polyphosphate inhibitor. From thrombin-antithrombin immunoassay of the effluent of blood flowing over collagen/TF, the majority of thrombin was found captured on intrathrombus fibrin. Additionally, extreme shear rates (>10,000 s-1) can generate massive von Willebrand Factor fibers that capture FXIIa and FXIa to drive fibrin generation, an event that facilitates VWF fiber dissolution under fibrinolytic conditions. Finally, we found that occlusive sterile thrombi subjected to pressure drops >70 mm-Hg/mm-clots have interstitial stresses sufficient to drive NETosis. These microfluidic studies highlight the interaction of contact pathway factors with the extrinsic pathway, platelet polyphosphate, VWF fibers, and potentially shear-induced NETs.